2016
DOI: 10.1002/jmri.25460
|View full text |Cite
|
Sign up to set email alerts
|

Application of texture analysis based on apparent diffusion coefficient maps in discriminating different stages of rectal cancer

Abstract: 3 J. MAGN. RESON. IMAGING 2017;45:1798-1808.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
112
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 35 publications
7
112
1
Order By: Relevance
“…Especially first‐order entropy correlated with overall stage with a correlation coefficient of 0.677, which was higher than ADC mean and ADC min ( r = –0.446, –0.437, respectively) in our previous study . Liu et al reported that first‐order entropy derived from the largest tumor slice of ADC map correlated with overall stage of rectal cancers ( r = 0.486), which was also weaker than the current study …”
Section: Discussioncontrasting
confidence: 90%
“…Especially first‐order entropy correlated with overall stage with a correlation coefficient of 0.677, which was higher than ADC mean and ADC min ( r = –0.446, –0.437, respectively) in our previous study . Liu et al reported that first‐order entropy derived from the largest tumor slice of ADC map correlated with overall stage of rectal cancers ( r = 0.486), which was also weaker than the current study …”
Section: Discussioncontrasting
confidence: 90%
“…This finding corresponds to previous studies in other malignant tumors, exemplarily clear cell renal cell carcinoma, and rectal cancer, which revealed that increased skewness of ADC histograms is associated with a more advanced disease stage [19,20]. Furthermore, an increase in ADC histogram skewness was observed in patients suffering from recurrent high grade glioma who showed disease progress under anti-proliferative chemotherapy, indicating ongoing proliferation of glioma cells within the tumor [21].…”
Section: Discussionsupporting
confidence: 89%
“…Radiomics features are quantitative descriptors that reflect textural variations in image intensity, shape, size, or volume to offer information on tumor phenotype, then these derived data can be mined for possible associations with underlying biology and reflect the behavior of malignant tumors . Successful applications of this technique have been performed on oncologic DWI datasets …”
mentioning
confidence: 99%